2021
DOI: 10.1186/s13229-020-00406-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-level analysis of molecular and neurobehavioral function in a prospective series of patients with germline heterozygous PTEN mutations with and without autism

Abstract: Background PTEN is a well-established risk gene for autism spectrum disorder (ASD). Yet, little is known about how PTEN mutations and associated molecular processes influence neurobehavioral function in mutation carriers with (PTEN-ASD) and without ASD (PTEN no-ASD). The primary aim of the present study was to examine group differences in peripheral blood-derived PTEN pathway protein levels between PTEN-ASD, PTEN no-ASD, and idiopathic macrocephalic ASD patients (macro-ASD). Secondarily, associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The pronounced variability and complexity in the profiles of NDD and NPD symptoms, cognitive processing, and adaptive abilities seen in individuals with PHTS (Balci et al, 2018; Busch et al, 2013, 2019; Frazier et al, 2015; Frazier et al, 2021; Hansen‐Kiss et al, 2017; Hobert et al, 2014; Steele et al, 2021; Uljarevic et al, 2021a, 2021b) and other NDGS (Agarwal et al, 2019; Arnett et al, 2018; Berryer et al, 2013; Jimenez‐Gomez et al, 2019; Mulder et al, 2020; Parker et al, 2015; Rai et al, 2018) present a significant assessment challenge. Although a range of currently available and widely‐used instruments have been developed to capture discrete clinical presentations in PHTS and other NGDS, including ASD, ADHD, internalizing and externalizing symptoms, these tools tend to evaluate either a single broad construct or only a subset of relevant symptoms or behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pronounced variability and complexity in the profiles of NDD and NPD symptoms, cognitive processing, and adaptive abilities seen in individuals with PHTS (Balci et al, 2018; Busch et al, 2013, 2019; Frazier et al, 2015; Frazier et al, 2021; Hansen‐Kiss et al, 2017; Hobert et al, 2014; Steele et al, 2021; Uljarevic et al, 2021a, 2021b) and other NDGS (Agarwal et al, 2019; Arnett et al, 2018; Berryer et al, 2013; Jimenez‐Gomez et al, 2019; Mulder et al, 2020; Parker et al, 2015; Rai et al, 2018) present a significant assessment challenge. Although a range of currently available and widely‐used instruments have been developed to capture discrete clinical presentations in PHTS and other NGDS, including ASD, ADHD, internalizing and externalizing symptoms, these tools tend to evaluate either a single broad construct or only a subset of relevant symptoms or behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Social communication/interaction, daily living skills, executive functioning, and quality of life levels tended to fall 1-2SD below the control mean, and motor skills fell more than 3SD below the control mean. The pronounced variability and complexity in the profiles of NDD and NPD symptoms, cognitive processing, and adaptive abilities seen in individuals with PHTS (Balci et al, 2018;Busch et al, 2013Busch et al, , 2019Frazier et al, 2015;Frazier et al, 2021;Hansen-Kiss et al, 2017;Hobert et al, 2014;Steele et al, 2021;Uljarevic et al, 2021aUljarevic et al, , 2021b and other NDGS (Agarwal et al, 2019;Arnett et al, 2018;Berryer et al, 2013;Jimenez-Gomez et al, 2019;Mulder et al, 2020;Parker et al, 2015;Rai et al, 2018) present a significant assessment challenge. Although a range of currently available and widely-used instruments have been developed to capture discrete clinical presentations T A B L E 2 Factor analysis results by survey scale.…”
Section: Group Profiles Across Net Scalesmentioning
confidence: 99%
“…The Pten gene plays a critical role in the development of dentate granule neurons of the hippocampus, thus determining the synaptic structure and function ( 36 ). Previous work from our laboratory and several others have reported that loss of Pten leads to ASD and alteration in neuronal morphology and physiological function ( 3 , 8 , 54 , 55 ). Conditional Pten KO using different Cre-recombinase delivery methods in mice led to neuronal hypertrophy, seizures, increased dendritic arborization, and increased spine density ( 7 , 8 , 56 , 57 ).…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, our findings also highlight areas for future investigations, including the mechanisms underlying behavioral problems. In particular, it will be crucial to utilize a multi-level approach to fully characterize the associations between PTEN pathway proteins with individual differences in cognitive, behavioral, and clinical profiles (31). In addition, prospective research should attempt to further understand the impact of both cognitive functioning and ASD traits and explore the role of factors such as emotion regulation, cognitive control and intolerance of uncertainty that have been shown as key risk factors across a range of psychopathologies, in both general clinical (32)(33)(34), ASD (35)(36)(37)(38)(39)(40)(41) and most recently PTEN (42) cohorts.…”
Section: Discussionmentioning
confidence: 99%